2017
DOI: 10.1088/2399-1984/aa69fb
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic antimicrobial therapy using nanoparticles and antibiotics for the treatment of multidrug-resistant bacterial infection

Abstract: Infections caused by multidrug-resistant (MDR) bacteria pose a serious global burden of mortality, causing thousands of deaths each year. Antibiotic treatment of resistant infections further contributes to the rapidly increasing number of antibiotic-resistant species and strains. Synthetic macromolecules such as nanoparticles (NPs) exhibit broad-spectrum activity against MDR species, however lack of specificity towards bacteria relative to their mammalian hosts limits their widespread therapeutic application. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 88 publications
(55 citation statements)
references
References 51 publications
2
53
0
Order By: Relevance
“…Furthermore, NPs can direct these to the bacterium–antibiotic interface for promoting efficient interaction 165. Combined administration of NPs with antibiotics as the treatment regimen can reduce the required amount of both antibiotics and NP, thereby reducing toxicity risks and synergistically enhancing the effects of their antimicrobial activities 166. In addition to tagged nanocarriers, stimuli‐responsive antibiotic releasing systems own the constituents to achieve stimuli‐triggered response and provide synergetic effects between the antibacterial content and exogenous stimuli.…”
Section: Nanomaterial‐integrated Diagnosis Prevention and Therapy Omentioning
confidence: 99%
“…Furthermore, NPs can direct these to the bacterium–antibiotic interface for promoting efficient interaction 165. Combined administration of NPs with antibiotics as the treatment regimen can reduce the required amount of both antibiotics and NP, thereby reducing toxicity risks and synergistically enhancing the effects of their antimicrobial activities 166. In addition to tagged nanocarriers, stimuli‐responsive antibiotic releasing systems own the constituents to achieve stimuli‐triggered response and provide synergetic effects between the antibacterial content and exogenous stimuli.…”
Section: Nanomaterial‐integrated Diagnosis Prevention and Therapy Omentioning
confidence: 99%
“…Lately by using biogenic synthesis method, Sangaonkar and Pawar (2018) conjugated small sized Ag-nanoparticles (5-30 nm) with tetracycline, and this compound displayed biocidal action against four of the seven bacteria tested [32]. The mechanism of action involved deregulation of main efflux pump (tolC) and downregulation of proteins responsible for assembling of (tolC) in E. coli outer membrane [33].…”
Section: Antibiotics Capped Nanoparticlesmentioning
confidence: 99%
“…Several classes of antimicrobial NPs and nano-sized carriers for antibiotic delivery have proven effective in treating infectious diseases, including antibiotic-resistant ones, in vitro as well as in animal models [117]. Very recently, we demonstrated that even multidrug-resistant bacterial infection can be treated by synergistic antimicrobial therapy using NPs and antibiotics [119]. NPs with different physicochemical properties use different pathways to attack the bacterial infection.…”
Section: Antibacterial Nanotechnologies To Combat Orthopedic Infecmentioning
confidence: 99%
“…5) [121,122]. We have thoroughly reviewed the antibacterial properties of a wide range of NPs [119]; readers are referred to that review for details on specific types of NPs and their corresponding mechanisms of action. Here, we will focus solely on NP platforms designed to impede the bacterial activity associated with orthopedic trauma surgery.…”
Section: Antibacterial Nanotechnologies To Combat Orthopedic Infecmentioning
confidence: 99%